Lung cancer reported as a benign lesion due to low‐dose chest computed tomography artefact: A case report. Issue 6 (27th July 2020) - Coughlan, Fionn; Saffar, Bann; McWilliams, Annette; Melsom, Stephen
Summary: CT imaging for lung cancer screening requires low dose technique. Low dose CT chest imaging is associated with an increased risk of artefacts, such as increased noise. We present a case where an artefact from the low dose technique lead to a lung cancer being erroneously reported as a benign hamartoma.